2018
DOI: 10.1186/s12948-018-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban air pollution and climate change: “The Decalogue: Allergy Safe Tree” for allergic and respiratory diseases care

Abstract: BackgroundAccording to the World Health Organization, air pollution is closely associated with climate change and, in particular, with global warming. In addition to melting of ice and snow, rising sea level, and flooding of coastal areas, global warming is leading to a tropicalization of temperate marine ecosystems. Moreover, the effects of air pollution on airway and lung diseases are well documented as reported by the World Allergy Organization.MethodsScientific literature was searched for studies investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 73 publications
0
22
0
1
Order By: Relevance
“…Allergic patients with manifestation of asthma, rhinitis and conjunctivitis had acute relapses during the COVID-19 emergency both due to the massive spring exposure to allergens and other triggering factors such as internal and external pollutants [10,13] and to the sudden interruption of current treatment, for fear that the same drugs could facilitate SARS infection. On the contrary, in the current state of knowledge, intranasal corticosteroid therapy for allergic rhinitis can be continued in patients with COVID-19 at the recommended posology [8,10].…”
Section: Patients With Asthma Rhinitis and Conjunctivitismentioning
confidence: 99%
“…Allergic patients with manifestation of asthma, rhinitis and conjunctivitis had acute relapses during the COVID-19 emergency both due to the massive spring exposure to allergens and other triggering factors such as internal and external pollutants [10,13] and to the sudden interruption of current treatment, for fear that the same drugs could facilitate SARS infection. On the contrary, in the current state of knowledge, intranasal corticosteroid therapy for allergic rhinitis can be continued in patients with COVID-19 at the recommended posology [8,10].…”
Section: Patients With Asthma Rhinitis and Conjunctivitismentioning
confidence: 99%
“…The epidemiological studies have demonstrated that exposure to air PM is associated with several chronic inflammatory diseases, including pulmonary dysfunction, cardiovascular disorder, skin diseases, allergy, and cancer [2][3][4][5][6][7]. Recently, a mouse study suggested that chronic PM2.5 exposure (1 h daily, 5 days/week, 3 months) caused the genotoxic and epigenotoxic effects on DNA of the liver, kidney, and lung [41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the impacts of PM on human health and the strategies for reducing PM production have become a main issue of concern to the public, government, and scientists [1]. PM exposure has been demonstrated as a major risk factor associated with pulmonary dysfunction, cardiovascular disorder, hepatic fibrogenesis, skin diseases, allergy, cancer, and even neurological disorders [2][3][4][5][6][7]. PM is a complex mixture, which includes polyaromatic hydrocarbons, organic toxins, metals, and biological materials [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 80 ] The urban population will likely be disproportionately affected because of the urban heat island effect since excess heat causes direct impairment on airway and increase the formation of O 3 . [ 81 ] A study from Southern Spain showed that the pollen season in urban areas was twice as long as that of rural environments. [ 82 ]…”
Section: Vulnerable Groupsmentioning
confidence: 99%